(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Abdomen wound dehiscence (abdominal burst) is a severe postoperative complication and is linked to increased morbidity, re‐operation, longer hospital stays and increased mortality. Patients with peritonitis have a high risk due to contamination of operative fields, systemic sepsis, poor wound healing and malnutrition. Understanding the causes, incidence, and modifiable risk factors in this population is critical, to guide peri-operative optimisation and targeted interventions to prevent incidence and enhance outcomes. Objective: To identify the causes, incidence and risk factors for a ruptured abdomen in those who present with peritonitis. Study design: Cross‑sectional observational study Place and Duration of study: This study was conducted at Rawal Institute of Health Sciences Islamabad Pakistan from March 2025 to March 2026 Methodology: Patients with clinical and operative diagnosis of peritonitis, who were presented in the emergency department, were consecutively included. Demographic data, clinical findings and operative diagnoses were recorded on pre‑designed proformas. Included in the analysis were the following recorded variables: age, sex, primary cause of peritonitis and potential risk factors for abdominal wound dehiscence (hypoalbuminemia, postoperative respiratory tract infection/cough, intra‑abdominal collection, anemia, and paralytic ileus and obesity (BMI >30). Data on outcomes such as the occurrence of a burst abdomen and final disposition recorded. The data were analysed for frequencies, percentages and common risk factors associated with the problem of burst abdomen. Results: 120 patients with acute peritonitis were involved. The mean age of the patients was 40 ± 6 year (range: 13–70 years). There were 80 (66.7%) male and 40 (33.3%) female patients. The incidence of "burst abdomen" was 36 (30.0%) patients. The distribution of causes of peritonitis was: typhoid ileal perforation n = 52 (43.3%), duodenal ulcer perforation n = 25 (20.8%), ruptured appendix n = 20 (16.7%), intestinal tuberculous ileal perforation n = 12 (10.0%), ruptured liver abscess n = 8 (6.7%), and colonic perforation n = 3 (2.5%). The commonest risk factors in 36 patients who had developed burst abdomen were hypoalbuminemia (24/36, 66.7%), postoperative respiratory tract infection/cough (15/36, 41.7%), intra‑abdominal collection (12/36, 33.3%), paralytic ileus (6/36, 16.7%), anemia (3/36, 8.3%), and obesity (BMI >30) (3/36, 8.3%). In all, 90 (75.0%) patients recovered without incident and the others had an "incident" course or needed further interventions. Conclusion: This population had typhoid ileal perforation as a common cause of peritonitis and nearly 1 in 3 patients had a burst abdomen. The most common associated risk factors were hypoalbuminemia, postoperative respiratory infection and intra‑abdominal collections. The prevalence of abdominal wound dehiscence in patients with peritonitis can be reduced with early recognition and optimisation of nutritional status, careful intra-abdominal drainage and careful monitoring of patients in the postoperative period.